PELATIHAN PENYUSUNAN LAPORAN KEUANGAN DIGITAL BERBASIS SYARIAH YANG BERKESINAMBUNGAN GUNA MENINGKATKAN KINERJA KEUANGAN UMKM BINAAN PONDOK PESANTREN AL MUBAAROK CARINGIN DI KOTA BANDUNG - Tarmidi, Didi; Hendiarto, R.Susanto; Paramudhita, Radea Respati; Sambas, Ivan Gumilar; Sunjana, Fadhlan Ridwana; Wini, Rima (Universitas Mataram, 2024)
Financial competency through training in preparing sharia-based digital financial reports is the main factor in improving financial performance and one of the assessments for the success of a company's financial performance. The preparation of sharia-based digital financial reports is carried out through a sharia-based digital accounting process. Sharia-based digital financial reports are carried out through the process of recording, classifying and summarizing all transactions at MSMEs assisted by the Al Mubarook Caringin Islamic Boarding School in Bandung City, in order to produce sharia-based digital financial reports that can be used for decision making for stakeholders. This training in preparing sharia-based digital financial reports is a Community Service activity carried out at the Al Mubaarok Caringin Islamic Boarding School in Bandung City. Sharia-based digital financial reporting competency is really needed by MSMEs in various cities/regencies in West Java. Financial reports will provide various benefits for the continuity of MSME businesses, especially the Al Mubarook Caringin Islamic Boarding School in Bandung City and generally in various cities/regencies in West Java. The benefits of sharia-based digital financial reports include, MSMEs can assess their company's financial performance, MSMEs have access to banking, MSMEs can, MSMEs can plan and control their financial budgets, West MSMEs can calculate their taxes, and MSMEs have sharia-based digital financial reports that can be applied in various Islamic boarding schools in West Java.